2022
DOI: 10.3390/ijms231911277
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Cell-Worm Approach to Search for Compounds Counteracting the Toxicity of Tau Oligomers In Vivo

Abstract: A clear relationship between the tau assemblies and toxicity has still to be established. To correlate the tau conformation with its proteotoxic effect in vivo, we developed an innovative cell-worm-based approach. HEK293 cells expressing tau P301L under a tetracycline-inducible system (HEK T-Rex) were employed to produce different tau assemblies whose proteotoxic potential was evaluated using C. elegans. Lysates from cells induced for five days significantly reduced the worm’s locomotor activity. This toxic ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In this study, we first showed the multitarget potential of Aβ1-6 A2V (D) by confirming that the peptide inhibited the in vitro aggregation of tau even in its mutated P301L form, known to be more prone to misfold. Next, employing C. elegans as a biosensor, we investigated the effect of Aβ1-6 A2V (D) on the proteotoxicity of tau isoforms [ 26 , 27 ]. This approach produced remarkable synergies, enabling us to have a deeper insight into the activity of the Aβ1-6 A2V (D).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we first showed the multitarget potential of Aβ1-6 A2V (D) by confirming that the peptide inhibited the in vitro aggregation of tau even in its mutated P301L form, known to be more prone to misfold. Next, employing C. elegans as a biosensor, we investigated the effect of Aβ1-6 A2V (D) on the proteotoxicity of tau isoforms [ 26 , 27 ]. This approach produced remarkable synergies, enabling us to have a deeper insight into the activity of the Aβ1-6 A2V (D).…”
Section: Discussionmentioning
confidence: 99%
“…To test our working hypothesis, in this study, we first evaluated the ability of the hexapeptide on the aggregation and stability of recombinant tau. To investigate the effect of Aβ1-6 A2V (D) on tau toxicity, we utilized Caenorhabditis elegans as a biosensor [ 25 27 ]. This nematode is capable of specifically detecting toxic tau assemblies, particularly oligomeric assemblies, even when administered exogenously, resulting in neuromuscular impairment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations